What Web Ads, Blurbs and Introductions Tell Potential Dictionary Buyers about Users, User Needs and Lexicographic Functions - Andersen, Birger (HERMES - Journal of Language and Communication in Business, 2012)
The present article deals with an investigation aimed at establishing the extent to which existing dictionaries provide potential dictionary buyers/borrowers with clear, unmistakable and easily understandable information about user need situations that might prompt consultation of the dictionary in question. The investigation analyses four monolingual English phrasal verbs dictionaries and five monolingual English specialised dictionaries. The primary sources of such information are identified as back cover blurbs of dictionaries, introductions to dictionaries and web ads for dictionaries. In the analysis, statements about user need situations extracted from these information sources are first classified as clear vs. unclear statements. The clear statements are then classified under the lexicographic function to which they are related. The results of the analysis disconfirm the hypothesis that the more well-defined and constrained the intended user group or groups for a given dictionary are, the more likely it is that the sources of information will provide the potential dictionary buyer/borrower with clear, unmistakable and easily understandable information about lexicographic function(s).